Perbandingan Usahatani Bawang Merah Sistem Konvensional Dengan Sistem Automatic Solar Blue Light Trap - Mohamad Nasirudin; Anggi Indah Yuliana; Rizka Mudyanti (University of Jember, 2022)
There are two types of shallot planting systems in Sudimoro Village: the conventional system and the Automatic solar blue light trap system. The conventional system is planting shallots with the general treatment being to apply only synthetic chemical pesticides, while the Automatic solar blue light trap system is planting shallots by applying synthetic chemical pesticides and applying Automatic solar blue light traps. The purpose of this study was to compare the conventional system of shallot farming and the automatic solar blue light trap application system in Sudimoro Village. The population of this study was all shallot farmers in Sudimoro Village, which amounted to 9 farmers, consisting of 5 conventional farmers and 4 farmers applying Automatic solar blue light traps. This study uses a quantitative descriptive approach. The results of this study can be seen that the value of the R/C ratio of the conventional system is 1.33, while the system applies the Automatic solar blue light trap 3.36. These results indicate that both shallot farming systems are feasible to cultivate. While the value of the B/C ratio for the conventional system is 0.33, while the system applies the Automatic solar blue light trap 2.36, these results indicate that the shallot farming in Sudimoro Village, the conventional system is not feasible to continue, while the system applying the Automatic solar blue light trap is feasible to be continued.